Monitoring wizyjny a bezpieczeństwo w szkołach i placówkach szkolno-wychowawczych .......... 93 - Kochańska, Małgorzata (Systemy bezpieczeństwa: Wymiar lokalny i państwowy, 2020)
In schools and educational institutions, video surveillance was to ensure the safety of the people who were in them. The main purpose was to increase the level and sense of security of the pupils and charges. Video surveillance systems are mainly financed from the state budget or from local government subsidies. In the years 2007-2009, systems were established in 7,882 schools in Poland, and in 2015 there were already approx. 11 000. Have they really improved safety at school and the facility? The studies carried out by the author and NIK do not give a clear answer. One of the criticisms made by the author is the number of accidents involving pupils in these years.